Examining the Relationship between Innovation Activity and Corporate Cooperation among Small and Medium-sized Business Operating in the Slovak ICT Sector - Renata Machova; Angelika Csereova; Eniko Korcsmaros (Marketing i Menedžment Innovacij, 2024)
The innovation process is a key factor in developing and maintaining competitiveness; therefore, the SME sector should focus on innovation as well. Examining the impact of corporate cooperation on innovation activity is a crucial element. The main goal of the research is to assess the innovative activity and corporate cooperation of micro enterprises and SMEs operating in the ICT sector. In accordance with the main goal of our research, a hypothesis was formulated regarding the relationship between participating in formal networks and innovative activity as follows: There is a relationship between innovation activity and corporate cooperation. We use descriptive statistical methods, i.e., unweighted and weighted arithmetic means, as well as a structural analysis method to test our hypothesis. To verify our subhypothesis H (1a), we had to examine the innovative activity of the domestic SMEs participating in the research. According to our second subhypothesis H (1b), we stated that innovative SMEs are more likely to be members of cooperation networks than noninnovative businesses are. The second subhypothesis H(1b) is accepted. However, we could not detect a significant difference or hostile behaviour among the innovative and noninnovative SMEs since both groups of companies participated in co-operation networks at a similar rate, as they were not members of formal co-operation networks. Since our third subhypothesis—the formal network co-operations influence the form of assistance used during innovation activity—supporting the main hypothesis was rejected, the main hypothesis was also rejected. Therefore, a significant relationship can be detected between innovation activity and corporate cooperation among domestic SMEs. Based on data analysis from research carried out at the beginning of 2021, Slovakia was ranked among moderate innovators based on the innovation performance of EU countries in 2019. If more companies were to participate in future research, it might be possible that a connection between corporate cooperation and innovation activity could also be discovered in Slovakia. A proposal was formulated based on the results of the primary data analysis. Since no significant relationship could be detected for these two factors, the obtained research results did not match, and the results were opposite to the results obtained during the Netnes epidemic.